2016
DOI: 10.1007/s12630-015-0576-8
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β gene variants are associated with QTc interval prolongation following cardiac surgery: a prospective observational study

Abstract: Background We characterized cardiac surgery-induced dynamic changes of the corrected QT (QTc) interval and tested the hypothesis that genetic factors are associated with perioperative QTc prolongation independent of clinical and procedural factors. Methods All study subjects were ascertained from a prospective study of patients who underwent elective cardiac surgery during August 1999 to April 2002. We defined a prolonged QTc interval as >440 msec, measured from 24-hr pre- and postoperative 12-lead electroca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
3
0
2
Order By: Relevance
“…25 More generally, we demonstrated that regardless of the specific disease involved,QTc prolongation was commonly observed in subjects with elevated C-reactive protein (CRP) levels from different inflammatory conditions (infective, immuno-mediated, other), also robustly correlating with IL-6 serum concentrations. 65 In addition, in a large study performed on 1716 subjects of the general population, Medenwald et al 66 found that after covariate adjustment soluble TNF-receptor-1 levels were associated with QTc duration in women, while Kertai et al 67 reported that high IL-1β expressing gene variants were independent predictors of postoperative QTc prolongation among 957 patients undergoing cardiac surgery.…”
Section: Inflammatory Cytokines Lqts and Tdp/scd Risk: Clinical Evidencementioning
confidence: 99%
“…25 More generally, we demonstrated that regardless of the specific disease involved,QTc prolongation was commonly observed in subjects with elevated C-reactive protein (CRP) levels from different inflammatory conditions (infective, immuno-mediated, other), also robustly correlating with IL-6 serum concentrations. 65 In addition, in a large study performed on 1716 subjects of the general population, Medenwald et al 66 found that after covariate adjustment soluble TNF-receptor-1 levels were associated with QTc duration in women, while Kertai et al 67 reported that high IL-1β expressing gene variants were independent predictors of postoperative QTc prolongation among 957 patients undergoing cardiac surgery.…”
Section: Inflammatory Cytokines Lqts and Tdp/scd Risk: Clinical Evidencementioning
confidence: 99%
“…This was different from a cohort study in the UK, which suggested a lower inflammatory burden may protect against QTc prolongation in patients with rheumatoid arthritis (RA) [ 6 ]. Another study also reported the possible contribution of IL-1β in modulating susceptibility to QTc prolongation after cardiac surgery [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Описанными характеристиками и обусловлена та его динамика, которую можно наблюдать из наших данныхпик концентрации маркера отмечался после завершения ИК, т. е. после наибольшего среди в сей операции патологического воздействия. В дальнейшем наблюдалось снижение концентрации и возращение к дооперационному уровню, что соотносится с результатами других аналогичных исследований [33]. IL-6 является маркером СВО c двой ным -про-и противовоспалительным действием и отличается разнообразием клеток, продуцирующих его (кардиомиоциты, фибробласты, эндотелиоциты) [34,35].…”
Section: динамика маркеровunclassified